Vascular ultrasound as a follow-up tool in patients with giant cell arteritis: a prospective observational cohort study - Haaversen, Anne C. B.; Brekke, Lene Kristin; Kermani, Tanaz A.; Molberg, Øyvind; Diamantopoulos, Andreas P. (Frontiers in Medicine, 2024)
To evaluate relapses in giant cell arteritis (GCA), investigate the utility of vascular ultrasound to detect relapses, and develop and assess a composite score for GCA disease activity (GCAS) based on clinical symptoms, ultrasound imaging activity, and C-reactive protein (CRP).Patients with GCA were prospectively followed with scheduled visits, including assessment for clinical relapse, protocol ultrasound examination, and CRP. At each visit, patients were defined as having ultrasound remission or relapse. GCAS was calculated at every visit.The study included 132 patients, with a median follow-up time of 25 months (interquartile range (IR) 21). The clinical relapse rate was 60.6%. There were no differences in relapse rates between GCA subtypes (cranial-GCA, large vessel (LV)-GCA, and mixed-GCA) (p = 0.83).Ultrasound yielded a sensitivity of 61.2% and a specificity of 72.3% for diagnosing GCArelapse in our cohort. In 7.7% of follow-up visits with clinical relapses, neither high CRP nor findings of ultrasound relapse were registered. In comparison, in 29.4% of follow-up visits, there was both a high CRP and findings of ultrasound relapse but no symptoms of clinical relapse.We found moderate sensitivity and specificity for ultrasound as a monitoring tool for relapse in this prospective cohort of GCA patients. The extent or subtype of vasculitis at the diagnosis did not influence the number of relapses. Based on a combination of clinical symptoms, elevated CRP, and ultrasound findings, a composite score for GCA activity is proposed.